Implementation of Blockchain Technology in Africa - Jepkoech, Jennifer; Anyembe, Shibwabo.C. (European Centre for Research Training and Development UK, 2019)
Africa is currently tackling challenges to technologies and innovation in its suitable development agenda.in the journey to embracing the blockchain technology, ICT plays a very vital role in addressing the challenges. The introduction of internet technology and the World Wide Web has brought with it changes in the interactive nature of people. One of the most outspoken changes is "Blockchain", a smart technology that allows people to transact without the need for an intermediary. In Africa, Blockchain is known as "the trusted machine" because one can be sure of doing clean transactions using blockchain. The technology behind "bitcoin" is the decentralized databases and cryptocurrency and its major merits are decentralization, security, and transparency, resistance to outages and efficiency. Almost all the sectors are using this technology some of which are; health, education, governance, financial institutions industries and IT. According to the firm Research and Markets 3 from the United States of America, the worldwide cryptocurrency and blockchain technology market will grow by 35.2 percent during the forecast period 2016–, to touch an aggregate of $42.16 billion by 2022. Most of this growth, however, will take place in the United States, followed by Europe, the Asia-Pacific, and India.
Keywords: Block chain; Bitcoin; Cryptocurrencies